Perbedaan Pengetahuan Ibu Hamil Tentang Kebutuhan Gizi Ibu Hamil Sebelum dan Sesudah Penyuluhan di desa Joho Kecamatan Wates Kabupaten Kediri - rofik - darmayanti (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2020)
ABSTRAC When pregnant mothers should eat foods that contain nutritional value of high quality does not mean expensive food. Nutrition at the time of pregnancy should be increased up to 300 calories per day (Walyani,2015:88). Compared to the mother is not pregnant, the need for the mother will increase protein 68%, folic acid 100%, calcium 50%, and iron 200-300% (Sukarni,2013:115. The purpose of this research is to know the knowledge difference of pregnant women about the nutritional needs of pregnant women before and after the counseling in the village Joho Wates District Kediri Regency. This research uses experimental methods. The population of all expectant mothers in the village of Joho Wates District Kediri 18 people. Sampling techniques use a total sampling. The variables of this research use in this study, free variables are counseling about nutritional needs in pregnant women. In this study, a bound variable is the knowledge of pregnant women about nutritional needs in pregnant women. Therefore, more active health officers are expected to provide counseling. Based on the results of the analysis Ha received which means there is a difference in the knowledge of pregnant women about nutritional needs in pregnant women before and after counseling. The results of the statistical test conducted by SPSS with the formula Wilcoxon Match Pairtest on 18 respondents calculated using the computer showed a Z value of-3,740 with a signification value (σ) of 0.000 (σ ≤ 0.05).